2021
DOI: 10.3389/fmed.2021.701789
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Biomarkers for the Diagnosis of Ankylosing Spondylitis: A Systematic Review and Meta-Analysis

Abstract: Background: Abnormal expression levels of microRNAs (miRNAs) were observed in ankylosing spondylitis (AS) in recent articles, suggesting that miRNAs may be used as biomarkers for AS diagnoses. In this paper, we conducted a meta-analysis to identify the overall diagnostic accuracy of miRNA biomarkers in AS patients.Methods: An extensive search was undertaken in PubMed, Embase, Cochrane databases, and Wan Fang database up to 30 December 2020 using the following key words: (“microRNAs” or “microRNA” or “miRNA” or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In IBD disease, exosomes can regulate mucosal barrier function and the immune ecology [ 53 ]. A meta-analysis showed that circulating miRNAs were dysregulated in AS patients [ 54 ]. In addition, one study showed that proinflammatory cytokines elevated miR-10b, which may function as a feedback loop to inhibit IL-17A by targeting MAP3K7.…”
Section: Discussionmentioning
confidence: 99%
“…In IBD disease, exosomes can regulate mucosal barrier function and the immune ecology [ 53 ]. A meta-analysis showed that circulating miRNAs were dysregulated in AS patients [ 54 ]. In addition, one study showed that proinflammatory cytokines elevated miR-10b, which may function as a feedback loop to inhibit IL-17A by targeting MAP3K7.…”
Section: Discussionmentioning
confidence: 99%